2018
DOI: 10.1186/s12978-018-0489-4
|View full text |Cite
|
Sign up to set email alerts
|

Thriving in scrubs: a qualitative study of resident resilience

Abstract: BackgroundPhysician well-being impacts both doctors and patients. In light of high rates of physician burnout, enhancing resilience is a priority. To inform effective interventions, educators need to understand how resilience develops during residency.MethodsA qualitative study using grounded theory examined the lived experience of resilience in residents. A cohort of obstetrics and gynecology residents were selected as a purposive, intensity sample.. Eighteen residents in all years of training participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 61 publications
1
66
0
8
Order By: Relevance
“…The final thematic coding phase generated an explanatory framework for the relationships between the categories. Initial analysis of the first interview data is described elsewhere . Insights from that analysis informed the conceptual model of resilience that was confirmed and expanded in this analysis (Figs.…”
Section: Methodsmentioning
confidence: 76%
See 2 more Smart Citations
“…The final thematic coding phase generated an explanatory framework for the relationships between the categories. Initial analysis of the first interview data is described elsewhere . Insights from that analysis informed the conceptual model of resilience that was confirmed and expanded in this analysis (Figs.…”
Section: Methodsmentioning
confidence: 76%
“…OBGYN residents managing these demands and performing well in the clinical environment are likely to have developed resilience. Initial analysis of these interviews suggested that resilience was strongly linked to professional identity, growing through engagement with adversity and fuelled by the resident's values as well as connections to others . This study represents continued engagement with this group over time to allow for circumstantial and seasonal variations, and also observe positive adaptations to earlier adversity .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…For doctors, the influence of social support in both a professional and a personal capacity were identified across the review as important factors in determining resilience. [24,[34][35][36][37][38][39][40][41] Quantitatively, Waddimba et al's [24] study of New York physicians that scored doctors for resilience and assessed unit characteristics reported that clinicians who worked on a smaller clinical unit (<5 practitioners) scored significantly lower for resilience than those who worked on larger units. Waddimba concluded from this that the social support of colleagues was an important determinant of a doctor's resilience.…”
Section: Personality Traits and Resiliencementioning
confidence: 99%
“…Interestingly, the potential for relationships with work colleagues to have a significant impact on staff resilience was evident in Ovans' (2015) study of over 800 employees in the UK where 75% of respondents reported that managing difficult people and office politics were the biggest drains on their resilience. While the link between resilience and both social support such as relationships with colleagues (Luthar, 2015) and self-care (Winkel, Honart, Robinson, Jones, & Squires, 2018) has been reported, further research on university staff resilience is needed.…”
Section: Discussionmentioning
confidence: 99%